2012
DOI: 10.1159/000335734
|View full text |Cite
|
Sign up to set email alerts
|

Posthepatectomy Bile Leakage: How to Manage

Abstract: Background: Biliary leakage after liver resection continues to be reported. Management of bile leakage has changed in recent years, with nowadays non-surgical procedures as the preferred treatment. Methods: Biliary leakage and management were assessed in 381 patients who underwent liver resection between January 2005 and April 2011. Results: The overall rate of biliary leakage after liver resection was 5.0%, with a higher incidence in patients who had undergone concomitant hepaticojejunostomy (HJ; 13.6 vs. 3.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
1
35
0
3
Order By: Relevance
“…More recent small series have shown that PTC and subsequent drainage for a variety of indications can be feasible in patients with nondilated bile ducts as well; the technical success rates were similar to those in patients with dilated bile ducts (91-100%) [17,19,20,21,22,23,24,25,26]. Several studies have described the management of biliary leakage both after hepaticojejunostomy or post-hepatectomy, however a PTBD was performed in the minority of patients [27,28]. To our knowledge, we report the largest study on only PTBD procedures for biliary leakage in a group of exclusively postoperative patients.…”
Section: Introductionmentioning
confidence: 99%
“…More recent small series have shown that PTC and subsequent drainage for a variety of indications can be feasible in patients with nondilated bile ducts as well; the technical success rates were similar to those in patients with dilated bile ducts (91-100%) [17,19,20,21,22,23,24,25,26]. Several studies have described the management of biliary leakage both after hepaticojejunostomy or post-hepatectomy, however a PTBD was performed in the minority of patients [27,28]. To our knowledge, we report the largest study on only PTBD procedures for biliary leakage in a group of exclusively postoperative patients.…”
Section: Introductionmentioning
confidence: 99%
“…The reported bile leak rate for this procedure was higher than the liver resection alone, and major hepatectomy and lymphadenectomy were considered as risk factors. 12,13 In our center the hepatoduodenal ligament lymph node dissection was performed routinely for malignancy and the extrahepatic biliary duct was skeletonized, which would destroy the blood supply of common hepatic duct partially. Meanwhile liver resection, especially for right hepatectomy, would make a further diminution of blood supply and prevent the healing of HJ anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Leak rates following laparoscopic cholecystectomy are now around 0.2% and so similar to the open area 10. Although less commonly performed operations, the rates of biliary leaks following liver resection and transplantation are reported to be in the order of 5% and 2–25% respectively 11 12…”
Section: Discussionmentioning
confidence: 99%